Effect of Vitamin C on some biological and immunological aspects of the honeybee, Apis mellifera L. - Maryiam M. Hussein; Mushtaq T. K. Al-Esawy (Journal of Kerbala for Agricultural Sciences, 2025)
The study evaluated the effect of adding different concentrations of vitamin C (2,4,8,16) mg on certain life aspects of honeybee workers, including consumption and survival rates. Additionally, it impacts immune indicators, such as encapsulation and melanization. The laboratory experiment results indicate that bees preferred adding vitamin C at a concentration of 2% to the nutritional feed in terms of consumption and survival rate. However, the concentration of 16% showed significantly lower consumption rates, but no differences were observed in the survival rate. The consumption rates were recorded as 108.81 and 9.48 mg/bee/day, respectively, while the survival rates were 98.57 and 93.72 %, respectively on concentrations 2and 16 mg . The bees' immune system was tested as a response to the regulation of protein and fat in the diet and vitamin C concentrations. The results showed a positive correlation between the encapsulation index and melanization activity, fat-to-protein ratio, and vitamin C concentrations. The maximum percentage of encapsulation index was (63.63 and 64.54) % in P: F and 8mg VC, respectively. Omit the minimum rate (54.07) % in 16mg VC.